Beyond knowledge: Confidence and the gender gap in financial literacy - Marius Cziriak; Tabea Bucher-Koenen; Rob Alessie (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Women are less likely to correctly answer the "Big-3" financial literacy questions, and a substantial share of the gap reflects women's lower confidence. In our experiment, women are more likely to choose "do not know" or refuse to answer financial literacy questions. If these options are not available, the gender gap decreases substantially. We build on the method proposed by Bucher-Koenen et al. (2021) and provide an easy-to-implement survey design applicable in cross-sectional studies that allows us to disentangle financial knowledge and confidence. We find that both financial knowledge and confidence are related to participation in the stock market.
Keywords: G53; C81; D14; D91; 330; financial knowledge; gender gap; financial decision making; measurement error; survey methodology